Religious education from a critical realist perspective: Sensus fidei and critical thinking - Go, Johnny C. (Routledge studies in critical realism, 2019)
Critical thinking in Catholic religious education -- Critical realism and Catholic Christianity -- A critical realist account of critical thinking -- An empirical investigation of teacher epistemologies -- A case for a critical realist Catholic religious epistemology -- Catholic religious critical thinking as the exercise of Sensus fidei.